Analisis Kapasitas Tampung Saluran Drainase Utama di Kawasan Perkantoran di Kabupaten Melawi - Kristovianus, Edwin; Nurhayati, Nurhayati; Andi, Uray Fery (Universitas Tanjungpura, 2024)
Flooding is a river flow that overflows natural or artificial dikes, thus inundating several areas, including the central office area. Flood control and prevention in the central office area can be done by analyzing hydrological conditions in the catchment area, where the central office area is in its area. One of the central office areas that often experience flooding is in Melawi Regency. The existing condition of the area is between 2 rivers, namely the Melawi River and the Pinoh River. This study aims to analyze the drainage system's capacity in the Melawi Regency office area. The study was conducted in Melawi Regency which is located at 0 °07' - 1 °21' South Latitude and 111 °07' - 112 °27' East Longitude. The data used are primary data and secondary data. The primary data used is the channel dimension. The secondary data used are rainfall, population, and topographic maps. The hydrological analysis was carried out, namely the analysis of rainfall intensity, waste discharge, and design discharge using the Rational method. The results showed that the largest design discharge was found in Region VII, which was 0.21272 m3/sec.